LAW ENFORCEMENT ANALYSIS OF ZTE WI-FI ROUTER THIEVERY - Amsori, Rachmad; Subekti; Suyono, Yoyok Ucuk (jfpublisher, 2023)
The crime of theft is regulated in Book II, Chapter XXII of Law Number 1 of 1946 concerning on the Criminal Code (KUHP) Articles 362 to Article 367. In this Chapter, five types of theft are regulated, such as Ordinary theft (Article 362) Criminal Code, Theft with weight (Article 363) of the Criminal Code, Minor theft (Article 364) of the Criminal Code, Theft with violence (Article 365) of the Criminal Code, and Theft in the family (Article 367) of the Criminal Code. The type of research used in this research is sociological or empirical legal research since, in this case, the researcher directly observes what is happening in society. Based on the research result, Surabaya District Court, which conducts criminal investigations and trials, has decided in the defendant's case, sentencing the Perpetrator of Theft of Zte Wi-FiRouter Based on Decision Number 2011/Pid.B/2022/PN Sby. According to panel of judges, the punishment imposed on the defendant as stated in the court decision has been deemed as appropriate and fair, both from the defendant's interests, society's interests, and the implementation of the law generally, that punishment is used as a last resort and not as an attempt to exact revenge for the perpetrator act.